Pengaruh Pendidikan Kewirausahaan dan Mental Berwirausaha terhadap Motivasi Berwirausaha pada Pelaku Usaha Aroepala Food City di Kota Makassar - Devi Gita Maharani; Agus Syam; Inanna Inanna; Tuti Supatminingsih; Muhammad Hasan (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. This study aims to determine the effect of Entrepreneurship Education and Entrepreneurial Mentality on Entrepreneurial Motivation in Aroepala Food City business actors in Makassar City. This study uses quantitative methods, data collection is done by means of a questionnaire distributed to 36 business actors in Aroepala Food City as a sample taken from the population. The population of this study is the business actor Aroepala Food City. The analysis technique used is descriptive analysis and multiple regression analysis. The results of this study indicate that: based on the results of the partial test, entrepreneurship education and entrepreneurship mentality each have a positive effect on the entrepreneurial motivation of Aroepala Food City business actors in Makassar City. Entrepreneurship education and entrepreneurship mentality simultaneously have a positive and significant effect on entrepreneurial motivation in Aroepala Food City business actors in Makassar City. Keywords: Entrepreneurship Education, Entrepreneurial Mental, Entrepreneurial Motivation